Boots of leather, slippers of gold: The history of a lesbian community - Lapovsky Kennedy, Elizabeth; Davis, Madeline D.. (Routledge, 2014)
Boots of Leather, Slippers of Gold traces the evolution of the lesbian community in Buffalo, New York from the mid-1930s up to the early 1960s. Drawing upon the oral histories of 45 women, it is the first comprehensive history of a working-class lesbian community. These poignant and complex stories show how black and white working-class lesbians, although living under oppressive circumstances, nevertheless became powerful agents of historical change. Kennedy and Davis provide a unique insider's perspective on butch-fem culture and argue that the roots of gay and lesbian liberation are found specifically in the determined resistance of working-class lesbians. This 20th anniversary edition republishes the book for a new generation of readers. It includes a new preface in which the authors reflect on where the last 20 years have taken them, and reminisce about the process of creating Boots of Leather, Slippers of Gold. For anyone interested in lesbian life during the 1950s, or in the dynamics of butch-fem culture, this study remains the one that set the highest standard for all oral histories and ethnographies of lesbian communities anywhere."-- Provided by publisher"Boots of Leather, Slippers of Gold traces the evolution of the lesbian community in Buffalo, New York from the mid-1930s up to the early 1960s. Drawing upon the oral histories of 45 women, it is the first comprehensive history of a working-class lesbian community. Kennedy and Davis provide a unique insider's perspective on butch-fem culture and argue that the roots of gay and lesbian liberation are found specifically in the determined resistance of working-class lesbians. This 20th anniversary edition includes a new preface by the authors
Keywords: amériques; discipline; histoire; identités LGBTQIA2+; ressource en ligne; régions géographiques; sciences humaines; états-unis